Preparation and characterization of copper (I) iodide thin films prepared by spin coating method at different molarities of solution / Muhammad ' Atiq Azman - Azman, Muhammad ' Atiq (2011)
This work will show the effect of using different moralities of solution on Cul thin films. The material that used in preparing thin film is Cul that have been synthesized using chemical vapor deposition method. The method used to deposit the solution onto the glass substrate for preparing thin film was spin coating technique. The purpose using glass substrate is for characterization the physical, electrical and optical properties. It was characterized by using Atomic Force Microscopy (AFM), UV-Vis-NIR measurement and two point probe I-V measurement. For physical properties, the nanostructure Cul thin films can be seen through AFM measurement. The value of transmittance, absorption coefficient and optical was concentrated on characterization the optical properties. Next for electrical properties, the main purpose is to study on its resistivity and conductivity.